Secondary students’ digital competence when searching and selecting scientific information - Daniel Valverde-Crespo; Antonio José De Pro Bueno; Joaquín González-Sánchez (Enseñanza de las Ciencias, 2020)
Nowadays, Internet is the first source of information on science and technology, and the development of competences for using this socially established tool is considered as desirable for the scientific literacy of citizens. For this reason, this study intends to describe the digital competences which are shown among students in the third year of Compulsory Secondary Education (ESO in Spanish), to search, select and use information on a scientific topic, more particularly, on acid rain. After applying a questionnaire, two different analysis techniques are used to assess the participants’ responses. We identify different sequences to search in network, to use the information and to assess it.